Hyperexpressed Netrin-1 Promoted Neural Stem Cells Migration in Mice after Focal Cerebral Ischemia - Lu, Haiyan; Song, Xiaoyan; Wang, Feng; Wang, Guodong; Wu, Yuncheng; Wang, Qiaoshu; Wang, Yongting; Yang, Guo-Yuan; Zhang, Zhijun (Frontiers in Cellular Neuroscience, 2016)
Endogenous Netrin-1 (NT-1) protein was significantly increased after cerebral ischemia, which may participate in the repair after transient cerebral ischemic injury. In this work, we explore whether NT-1 can be steadily overexpressed by AAV and the exogenous NT-1 can promote neural stem cells migration from the subventricular zone (SVZ) region after cerebral ischemia. Adult CD-1 mice were injected stereotacticly with adeno-associated virus carrying NT-1 gene (AAV-NT-1). Mice underwent 60 minutes of middle cerebral artery occlusion one week after injection. We found that NT-1 mainly expressed in neuron and astrocyte, and the expression level of NT-1 significantly increased one week after AAV-NT-1 gene transfer and lasted for 28 days, even after tMCAO as well (p＜0.05). Immunohistochemistry results showed that the number of neural stem cells was greatly increased in the SVZ region of AAV-NT-1-transduced mice compared with control mice. Our study showed that overexpressed NT-1 promoted neural stem cells migration from SVZ, this result suggested that NT-1 is a promising factor for repairing and remodeling after focal cerebral ischemia.